Intermediate pressure-normalized principal wall strain values are associated with increased abdominal aortic aneurysmal growth rates - Zottola, Zachary R.; Kong, Daniel S.; Medhekar, Ankit N.; Frye, Lauren E.; Hao, Scarlett B.; Gonring, Dakota W.; Hirad, Adnan A.; Stoner, Michael C.; Richards, Michael S.; Mix, Doran S. (Frontiers in Cardiovascular Medicine, 2023)
Current abdominal aortic aneurysm (AAA) assessment relies on analysis of AAA diameter and growth rate. However, evidence demonstrates that AAA pathology varies among patients and morphometric analysis alone is insufficient to precisely predict individual rupture risk. Biomechanical parameters, such as pressure-normalized AAA principal wall strain (𝜺 𝝆+ /PP, %/mmHg), can provide useful information for AAA assessment. Therefore, this study utilized a previously validatedour novel ultrasound elastography (USE) technique to correlate 𝜺 𝝆+ /PP with the current AAA assessment methods of maximal AAA diameter and growth rate.Our USE algorithm utilizes a finite element mesh, overlaid a 2D cross-sectional view of the userdefined AAA wall, at the location of maximum diameter, to track two-dimensional, frame-to-frame displacements over a full cardiac cycle, using a custom image registration algorithm to produce 𝜺 𝝆+ /PP. This metric was compared between patients with healthy aortas and AAAs (≥3cm) and compared between small and large AAAs (≥5cm). AAAs were then separated into terciles based on 𝜺 𝝆+ /PP values to further assess differences in our metric across maximal AAA diameter and prospective growth rate. Non-parametric tests of hypotheses Mann Whitney U and Kruskal-Wallis tests were used to assess statistical significance as appropriate. This is a provisional file, not the final typeset articleUSE analysis was conducted on 129 patients, 16 healthy aortas and 113 AAAs, of which 86 were classified as small AAAs and 27 as large. Non-aneurysmal aortas showed higher 𝜺 𝝆+ /PP compared to AAAs (0.044±0.015 vs. 0.034±0.017 %/mmHg, p=0.01) indicating AAA walls to be stiffer. Small and large AAAs showed no difference in 𝜺 𝝆+ /PP. When divided into terciles based on 𝜺 𝝆+ /PP cutoffs of 0.0251 and 0.038 %/mmHg, there was no difference in AAA diameter. There was a statistically significant difference in prospective growth rate between the intermediate tercile and the outer two terciles (1.46±2.48 vs 3.59±3.83 vs 1.78±1.64 mm/yr, p=0.014).